Um modelo para gestão de transferência de conhecimento e tecnologia para estágio acadêmico - Luz, Andréia Antunes da (2017)
This research objected to define a management model for the academic internship, with an approach in Knowledge Management and Knowledge and Technology Transfer. The methodological procedures, classified as applied, qualitative, descriptive, bibliographical, documentary and survey, were utilized as an object of study by the Academic Internship. Moreover, the Methodi Ordinatio was employed in the construction of the portfolio. The portal prototype acts as a repository for the internship, with an interaction interface for the intern, professor, supervisor, education institution, firm, integration agent, and external users. Its acting enables the extraction, memorization, sharing, and reuse of knowledge and technology, protecting them and broadening the intern's ability to discover and innovate, based on the collaborative tools of knowledge management available to all users registered in the portal. The paths toward intellectual capital development and innovation in products, processes and services, converting individual knowledge into collective knowledge, will transform the users into, simultaneously, consumers and creators of knowledge and technology, with learning support and no time or place limitations, providing at the same time knowledge and learning to the student. The viewpoints of students, coordinators and internship supervisors confirm that the portal's utilization in internships can transfer and store knowledge with an interface of influence and interaction. The portal prototype presents an innovative internship management process, proving that this environment allows user needs to arise, and contributes to the student/intern's learning process, systematizing the practical knowledge and technology acquired and experienced in the internship. This research contributes to the reformulation of the Internship Management System.